2020
DOI: 10.1088/1361-6641/ab7146
|View full text |Cite
|
Sign up to set email alerts
|

Study of random dopant fluctuation in PNPN feedback FET

Abstract: The impact of random dopant fluctuation (RDF) on the performance variation of a PNPN feedback field effect transistor (PNPN FBFET) is investigated using a 3D technology computer aided design tool. To investigate RDF-induced device performance variation (e.g. threshold voltage (V TH ) variation), the nominal doping profile of each region in a PNPN FBFET is separately randomized. Consequently, in terms of RDF-induced V TH variation, the channel-2 region (i.e. gated channel region) plays a key role as a main cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Therefore, research related to device optimization techniques and physics analysis is required to include latchup voltage and threshold voltage variations. Furthermore, the large memory window variation owing to the latch-up characteristics sensitive to the channel length and doping concentrations degrades the memory performance [17][18][19][20][21][22][23][24][25]. The channel length changes the current gain in coupled bipolar junction transistors (BJTs) within an FBFET, which induces variations in the latch-up and threshold voltages [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research related to device optimization techniques and physics analysis is required to include latchup voltage and threshold voltage variations. Furthermore, the large memory window variation owing to the latch-up characteristics sensitive to the channel length and doping concentrations degrades the memory performance [17][18][19][20][21][22][23][24][25]. The channel length changes the current gain in coupled bipolar junction transistors (BJTs) within an FBFET, which induces variations in the latch-up and threshold voltages [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In order to use FBFETs in next-generation electronics, it is essential to examine their reliabilities under various conditions, including temperature and gate-bias stresses. To date, studies on the reliabilities have been conducted using simulation models to determine the dependence of their electrical properties on temperature [9][10][11]. Nevertheless, there has not been any research reported on their electrical stability under gate-bias stresses.…”
Section: Introductionmentioning
confidence: 99%